1996
DOI: 10.1007/bf01292622
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of fluoxetine on the locomotor hyperactivity induced by MK-801, a non-competitive NMDA receptor antagonist

Abstract: It was found previously that the MK-801 (an uncompetitive NMDA receptor antagonist)-induced locomotor hyperactivity in rats was potently increased by antidepressant drugs. The present paper analysed the locomotor hyperactivity induced by combined treatment with fluoxetine + MK-801 in male Wistar rats. The MK-801 hyperactivity was increased by citalopram (the latter effect was prevented by zacopride and ketanserin), sertraline, p-chloramphetamine, 8-OH-DPAT and TFMPP. The hyperlocomotion caused by fluoxetine + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
(45 reference statements)
0
16
1
Order By: Relevance
“…The results of the present study stand in contrast to those previously reported by Callaway et al (1990) and Maj et al (1996), who found that fluoxetine did not affect the locomotor response to amphetamine. However, in those studies fluoxetine was administered 60 and 120 min, respectively, before the amphetamine treatment while in the present study fluoxetine was administered 30 min prior to treatment with amphetamine.…”
Section: Figcontrasting
confidence: 86%
“…The results of the present study stand in contrast to those previously reported by Callaway et al (1990) and Maj et al (1996), who found that fluoxetine did not affect the locomotor response to amphetamine. However, in those studies fluoxetine was administered 60 and 120 min, respectively, before the amphetamine treatment while in the present study fluoxetine was administered 30 min prior to treatment with amphetamine.…”
Section: Figcontrasting
confidence: 86%
“…It is noteworthy that some experiments failed to observe an interaction between MK-801 and WAY 100135 at a level of locomotor activity (Maj et al 1996). This discrepancy may result from two facts.…”
Section: Locomotor Activitymentioning
confidence: 41%
“…This discrepancy may result from two facts. First, the effect of WAY 100135, however strong, is transient and may be obscured by the potent long-lasting stimulatory effect of MK-801, especially when results are presented in a cumulative manner (Maj et al 1996). Secondly, in the present study we used an experimental procedure which differentiated between locomotion and stereotyped behavior ȩ ȩ concomitant with locomotor hyperactivity, the latter being unaffected by WAY 100135.…”
Section: Locomotor Activitymentioning
confidence: 99%
“…However, since Willins et al (1992) found that 1 g/side of DNQX decreased the locomotor response to 0.5 mg/kg AMPH, it may be that DNQX has unique effects on METH stimulated behavior. Serotonin releasing agents have been shown to synergistically enhance the locomotor activating properties of GLU antagonists (Maj et al 1996). METH is known to be more effective at releasing serotonin than AMPH .…”
Section: Discussionmentioning
confidence: 99%